Association of body image with the consumption of sugary drinks and nutritional status in adolescents - Souzalima Caldoncelli Franco, Frederico; Antunes Faria Carraro, Renan; Azevedo Cabral, Thalita; Santos Marques, Juliana (O Mundo da Saúde, 2020)
The consumption of sugary drinks has increased and may affect weight and body image; however, little is known about the relationship of body satisfaction with the intake of these drinks. This study aimed to evaluate the association of body image with the consumption of sugary drinks and nutritional status in adolescents. 42 students of an integrated technical education were evaluated according to the silhouette scale, consumption of sugary drinks, and anthropometric parameters. The data were analyzed by ANOVA and Chi-squared tests and categorized by body satisfaction. Most adolescents were eutrophic (83.3%) but showed a high level of body image dissatisfaction (boys: 65.2% and girls: 63.1%). Sugary drinks are consumed by 73.8 to 88.1% of those evaluated. Artificial juice and soft drinks were the most consumed beverages for 2-5x/week at school for having a pleasant taste and practicality and were predominantly ingested by adolescents dissatisfied with being overweight. According to the silhouette scale, 52.4% of students reported body image equal to the BMI/age classification, however, 33.3% overestimated and 14.3% underestimated their body image. Girls showed a higher overweight estimate than boys (42.1 vs. 26.1%). Body weight, BMI and waist and abdomen circumferences were greatest in overweight students, as well as being associated with dissatisfaction with overweight. It was concluded that artificial juice and soda were the most consumed sugary drinks by adolescents dissatisfied with being overweight. Overestimation of body image was presented at a high level, suggesting the need for educational intervention in this population.